Eco Tourism as a Recreational Impact Factor on Human Condition - TRETYAKOVA, Tatyana; SAVINOVSKAYA, Anastasia (Journal of Environmental Management and Tourism; Vol 7 No 1 (2016): JEMT Volume VII, Issue 1(13) Spring 2016, 2016)
This set of our research problem, which is to find ways of eco-tourism impact on the physiological and psycho-emotional state of a person, increasing his resistance to stress, emotional recovery, well-being, mood, etc. The purpose of research is to identify the nature of eco-tourism’s recreational facilities on the basis of state of tourists monitoring during a trip. The object of the study is a tourist, as the subject of eco-tourism. The subject of research is the list of recreational changes in tourists’ state in ecological tour conditions. The research hypothesis is the following: the tourists’ state in the environmental tour conditions will demonstrate positive dynamics of the psycho-emotional and physiological state as a result of the natural conditions’ impact, which will allow us to introduce such recreational term as "Eco therapy". The study showed that there is a little change in the tourists’ hemodynamics and heart rate in the end of the Ay River rafting as a form of ecological tour. Both males’ and females’ blood pressure and heart rate remain in the normal range and meet the normal state throughout the tour. The group’s emotional state self-esteem and the level of anxiety and depression entered the set limit and are at a high level, indicating the favorable and positive impact of travel on the human body.
Keywords: ecological tourism, rafting, anxiety and depression level